Fathers parenting role: self-esteem, parenting styles and parental self-efficacy - Pires, Mónica (2013)
This study aims to explore the relation between fathers parenting styles (PS), self-esteem (SE) and parental self-efficacy (PSE). Research points out the complex potential relations between SE and PSE. Although PSE has been studied in association to PS, there’s a research gap concerning the influence of fathers’ SE in this process. In a cross-sectional study a questionnaire comprising personal data, PS, SE and PSE was completed by 157men (age: M=38.41, SD=6.03) of pre-school/school age children. Hierarchical multiple regression analyses and structural equation models (SEM) were performed. Like other studies, authoritative PS is associated to positive outcomes, explaining 25% of PSE variance, in opposition to permissiveness, associated to a negative sense of PSE. Education level and SE emerge as significant predictors for fathers PS exerting indirect effects on PSE. Father’s higher levels of SE and education are important individual variables to fathers-child relation with implications on family affective climate and health.